2007
DOI: 10.1038/ng2025
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the MYB oncogene in T cell acute lymphoblastic leukemia

Abstract: We identified a duplication of the MYB oncogene in 8.4% of individuals with T cell acute lymphoblastic leukemia (T-ALL) and in five T-ALL cell lines. The duplication is associated with a threefold increase in MYB expression, and knockdown of MYB expression initiates T cell differentiation. Our results identify duplication of MYB as an oncogenic event and suggest that MYB could be a therapeutic target in human T-ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
200
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(212 citation statements)
references
References 13 publications
10
200
1
Order By: Relevance
“…This is surprising because there is generally strong correlation between transactivation and transformation by c-Myb (Hu et al, 1991), and the importance of functional co-activation by CBP/p300 (Pattabiraman et al, 2009) and menin/MLL (Jin et al, 2010) has been shown. In cancers linked to aberrations involving the MYB locus, increased c-Myb dosage, and hence activity, seems to be a common theme (Clappier et al, 2007;Lahortiga et al, 2007;Persson et al, 2009). Nevertheless, the 2KR and ANAA mutants described here seem to partially dissociate transactivation from transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising because there is generally strong correlation between transactivation and transformation by c-Myb (Hu et al, 1991), and the importance of functional co-activation by CBP/p300 (Pattabiraman et al, 2009) and menin/MLL (Jin et al, 2010) has been shown. In cancers linked to aberrations involving the MYB locus, increased c-Myb dosage, and hence activity, seems to be a common theme (Clappier et al, 2007;Lahortiga et al, 2007;Persson et al, 2009). Nevertheless, the 2KR and ANAA mutants described here seem to partially dissociate transactivation from transformation.…”
Section: Discussionmentioning
confidence: 99%
“…This can be caused by translocation, leading to deregulation of the MYB gene, as in childhood T-cell acute lymphoblastic leukemia (Clappier et al, 2007), or stabilization of MYB mRNA, as in adenoid cystic carcinomas of the breast, head and neck (Persson et al, 2009). Local duplication of MYB has also been reported with another subgroup of T-cell acute lymphoblastic leukemia (Clappier et al, 2007;Lahortiga et al, 2007) and in a subgroup of acute myelomonocytic leukemia (Murati et al, 2009). Thus, deregulation of c-Myb expression is associated with oncogenicity.…”
mentioning
confidence: 99%
“…Although isolated cases of amplification and truncation of MYB have also been described some time ago in human leukemias (8,9), the use of newer, higher-resolution genomic technologies is suggesting that MYB contributes more frequently to these diseases. Thus, chromosomal translocation and genomic duplications of MYB have been identified in human T-cell acute leukemia (10,11); more recently, a gain of the MYB locus has been reported in acute myelomonocytic leukemia (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, expression is also detected in smooth muscle cells [199], gut epithelium [200], hair follicles [201] and several non-hematopoietic carcinomas such as small cell lung carcinoma [202], colon carcinoma [203], breast carcinoma [204], and neuroblastoma [205], as well as Tcell acute lymphoblastic leukemia [206,207]. Interestingly, expression of Myb mRNA is abundantly expressed in hematopoietic progenitor cells and expression decreases as cells approach terminal differentiation [194,[208][209][210].…”
Section: Expression and Function Of Myb During Hematopoiesismentioning
confidence: 99%
“…Proper expression of c-Myb appears to be critical for normal thymopoiesis. Gene duplication of Myb or translocation of the Myb locus into the Tcrb locus is detected in patients with T-cell acute lymphoblastic leukemia (T-ALL), a neoplastic disorder of progenitor T cells [206,207]. The Myb-Tcrb translocation, which defines a new subset of T-ALL, places Myb expression under the control of Tcrb regulatory elements suggesting that continuous expression of c-Myb during thymopoiesis had an adverse effect characterized by increased expression of genes involved in cellular proliferation [206].…”
Section: Expression and Function Of Myb During Hematopoiesismentioning
confidence: 99%